Analisis Geopolitik dan Geostrategi Indonesia Terhadap Kebijakan Penghentian Ekspor Timah Indonesia di Pasar Global - Elysabet, Elysabet; Hadiwijoyo, Suryo Sakti (Jurnal Ilmiah Widya Sosiopolitika; Vol 5 No 2 (2023): DIPLOMASI DAN ISU-ISU INTERNASIONAL, 2023)
Indonesia is the world’s second largest producer of tin. As a world mineral supply country, Indonesia cooperates on a regional, bilateral, and multilateral scale. This brings benefits to Indonesia because there is income for the country that will be used for the domestic economy and development. However, tin exports must be increased downstream so that there is added value to the economy. The aim of this article is to examine the policy of stopping tin exports in Indonesia which has caused international reactions from various countries that need tin raw materials so that it has an impact on geopolitical turmoil for Indonesia. Qualitative data collection and literature review methods are used in this research. The findings explain the geopolitical dynamics of tin raw material exports and the strategies carried out by Indonesia through the tin export suspension policy in the global market.